Engineering valley polarization of monolayer WS2 : a physical doping approach - Feng, Shun (2020)
The emerging field of valleytronics has boosted intensive interests in investigating and controlling valley polarized light emission of monolayer transition metal dichalcogenides (1L TMDs). However, so far, the effective control of valley polarization degree in monolayer TMDs semiconductors is mostly achieved at liquid helium cryogenic temperature (4.2 K), with the requirements of high magnetic field and on‐resonance laser, which are of high cost and unwelcome for applications. To overcome this obstacle, it is depicted that by electrostatic and optical doping, even at temperatures far above liquid helium cryogenic temperature (80 K) and under off‐resonance laser excitation, a competitive valley polarization degree of monolayer WS2 can be achieved (more than threefold enhancement). The enhanced polarization is understood by a general doping dependent valley relaxation mechanism, which agrees well with the unified theory of carrier screening effects on intervalley scattering process. These results demonstrate that the tunability corresponds to an effective magnet field of ≈10 T at 4.2 K. This work not only serves as a reference to future valleytronic studies based on monolayer TMDs with various external or native carrier densities, but also provides an alternative approach toward enhanced polarization degree, which denotes an essential step toward practical valleytronic applications.